O10.5 Patterns of HIV pre-exposure prophylaxis care one year after initiating PrEP, baltimore city, maryland 2015–2018. (14th July 2019) - Wu, Linxuan; Schumacher, Christina; Chandran, Aruna; Fields, Errol; Davis, Maisha; Ryscavage, Patrick; Jones, Joyce; Page, Kathleen; Arringon-Sanders, Renata; Tepper, Vicki; Farley, Jason; Greenbaum, Adena; et al.
Abstract : Background: Persistent HIV pre-exposure prophylaxis (PrEP) use is critical to preventing HIV acquisition. U.S. Centers for Disease Control and Prevention (CDC) recommends quarterly clinical evaluation for individuals using PrEP. Individual-level adherence to quarterly PrEP-care visits is largely unknown. Our objective was to describe patterns of quarterly PrEP-care visit attendance among individuals enrolled in a large demonstration project to increase PrEP delivery in Baltimore City, Maryland. Methods: The project was a collaboration between a city health department, an academic evaluation partner, 6 clinical sites and one community based organization (CBO). Demographic and quarterly PrEP-care visit information from individuals initiating PrEP between October 1, 2015 and August 31, 2017 was abstracted from medical records using standardized forms. Participants were followed for one year. PrEP-care was categorized as 'Persistent' (attending all quarterly PrEP-care visits), 'Episodic' (missing > 1 PrEP-care visit and re-engaging PrEP-care visit), or 'Discontinued' (lost to follow-up after missing > 1 PrEP-care visit). Results: During the study period, 333 individuals initiated PrEP, among whom 52.9% (176) were Black/African-American, 82.3% (274) cisgender male, 73.6% (245) men who have sex with men (MSM), and 47.7% (159) aged 25–24 years. 9.0% (30), 40.5% (135), and 50.5% (168) were persistent, episodic and discontinued PrEP-care users, respectively. Over half (51.1%, 69/135) of episodic users missed the first quarterly visit; mean time to PrEP re-engaging was 6.3 months (SD: 2.18). About half (45.2%, 76/168) of those discontinuing PrEP-care did so within 3-months. Conclusion: Over one year, < 10% of individuals initiating PrEP were persistently in PrEP-care, and half discontinued PrEP-care completely. This suggests PrEP's effectiveness in reducing HIV transmission in Baltimore City may be limited. Future work should focus on identifying individual and structural barriers and facilitators to discontinuing PrEP-care and factors associated with re-engaging PrEP-care to inform interventions to improve persistent PrEP-care, and decrease ongoing HIV transmission. Disclosure: No significant relationships.